Pengaruh Penerapan Anggaran Berbasis Kinerja dan Penerapan Good Governance terhadap Akuntabilitas Kinerja Instansi Pemerintah - Nadira Hilmi Israr; Efrizal Syofyan (Universitas Negeri Padang, 2022)
The study aims to determine the effect of performance-based budgeting implementation and good governance implementation on the government performance accountability. The type of research used in this study is quantitative by using multiple linear regression with SPSS 25. The research result from regression analysis, performance-based budgeting implementation and good governance implementation had positive effect on the government performance accountability. In line with there was R2of 0,509 or 50,9%. It meant the contribution from performance-based budgeting implementation and good governance implementation reflected the government performance accountability of 49,1% while the rest of 49,1% was explained by other variables outside the research.